LEARNING STRATEGIES FOR SLOW LEARNERS USING THE PROJECT BASED LEARNING MODEL IN PRIMARY SCHOOL - Hartini, Ayu; Widyaningtyas, Dessy; Mashluhah, Mai Istiqomatul (Jurusan Pendidikan Luar Biasa)
Children with slow learning problem or a slow learner are those who have low learning achievement or slightly below average of children in general. Today, the children slowly learn many encountered not only in school inclusion, but in regular schools too. Teachers who do not have adequate experience will find it difficult to deal with in the classroom. So the goal of this research is to find appropriate learning strategies for slow learners in elementary school.Â